2014
DOI: 10.1001/jamaophthalmol.2014.2350
|View full text |Cite
|
Sign up to set email alerts
|

Disorganization of the Retinal Inner Layers as a Predictor of Visual Acuity in Eyes With Center-Involved Diabetic Macular Edema

Abstract: IMPORTANCE Biomarkers that predict future visual acuity (VA) in eyes with baseline diabetic macular edema (DME) would substantively improve risk assessment, management decisions, and selection of eyes for clinical studies targeting DME.OBJECTIVE To determine whether baseline or early change in the novel spectral domain-optical coherence tomography (SD-OCT) parameter disorganization of the retinal inner layers (DRIL) is predictive of VA in eyes with center-involved DME.DESIGN, SETTING, AND PARTICIPANTS At a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
381
4
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(413 citation statements)
references
References 12 publications
15
381
4
13
Order By: Relevance
“…Standard treatment for DME involves repetitive, invasive intraocular injections, increasing the burden on patients, physicians and healthcare resources [35]. Biomarkers that could predict the effect of a therapy on future VA in eyes with DME could improve risk assessment, management decisions, and selection of eyes for clinical studies [35].…”
Section: Discussionmentioning
confidence: 99%
“…Standard treatment for DME involves repetitive, invasive intraocular injections, increasing the burden on patients, physicians and healthcare resources [35]. Biomarkers that could predict the effect of a therapy on future VA in eyes with DME could improve risk assessment, management decisions, and selection of eyes for clinical studies [35].…”
Section: Discussionmentioning
confidence: 99%
“…OCT allows quantitative measurements of retinal thickness, as well as evaluation of morphologic changes in eyes with DR and DME. Potential neuroretinal biomarkers of visual acuity in eyes with DME based on OCT imaging have been suggested, including ganglion cell layer thinning, disorganization of the retinal inner layers, and photoreceptor disruption, although further validation is needed (44)(45)(46)(47). Recently, the technique of OCT angiography has also been utilized to create high-resolution perfusion maps of the central retinal vasculature (48).…”
Section: Evaluating the Diabetic Retinamentioning
confidence: 99%
“…Other studies have demonstrated changes in the outer retinal microstructures related to VA and to visual fields [11]. Such evaluations have been conducted for diabetic patients but included patients with varying treatments and disease durations [5]. Visual outcome prediction by pretreatment photoreceptor integrity has been discussed in naïve diabetes mellitus patients receiving triamcinolone injection [12].…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentation of ellipsoid and interdigitation lines was found to be associated with visual impairment in several retinal diseases such as ME, macular holes, epiretinal membranes, occult macular dystrophy and acute zonal occult outer retinopathy [3,5]. Direct assessment of photoreceptor microstructure integrity (ellipsoid and interdigitation zones) may also serve as a prognostic marker of treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation